Genetic engineering of Saccharomyces cerevisiae for efficient expression and secretion of glucoamylase and a-amylase - D'Aguanno, Vincenzo Silvano (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.